The Contamination of Staphylococcus aureus in Ready-to-eat Foods Sold Along the Old Roadside and New Roadside in Front of Champasack University Champasack Province - PHIMMASONE, odai; PHOUTTHABOUNMA, Souliya; PHOUTTHABOUNMA, Souliya; SAIYALARD, Sengchan; SYSOUPHAN, Ketmany; PHUTTHAVONG, Hatsady (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The study contamination of Staphylococcus aureus in ready-to-eat foods sold along the old roadside and new roadside in front of Champasack University, Champasack Province, this study examined the enumeration of Staphylococcus aureus in ready-to-eat foods using the spread plate technique, samples were collected between August and October 2025, the sample group consisted of 12 stores, with a total of 48 samples representing 4 kinds of foods. The findings of this study revealed contamination of Staphylococcus aureus in ready-to-eat foods revealed that among the 30 positive samples showed detected values between of 0 CFU/g to 4,900 CFU/g and 15 samples exceeded the microbiological control standards of the Ministry of Health, Department of Food and Drug Safety, Laos, showed detected values between 150 to 4,900 CFU/g, these detected values pose a direct health risk to consumers.